Realtime Web Apps With HTML5 WebSocket, PHP, and jQuery - Lengstorf, Jason; Leggetter, Phil.; Newman, Alex.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Realtime Web Apps: With HTML5 WebSocket, PHP, and jQuery is a guide for beginner- to intermediate-level web developers looking to take the next leap forward in website and app development: realtime. With Realtime Web Apps, you’ll be able to quickly get up to speed on what HTML5 WebSocket does, how it is going to affect the future of the web as we know it, and—thanks to Pusher’s simple API—start developing your first realtime app today. Using a practical approach rather than focusing on dry theory, Realtime Web Apps will guide you through building your first app using HTML5, CSS3, jQuery, and Pusher. After your initial introduction to the technologies used in the book, you’ll immediately jump into the process of creating a realtime Q&A app that will work on desktop browsers as well as mobile phones (including iOS and Android). In addition to learning realtime development strategies, you’ll also learn progressive development strategies including responsive CSS3 layouts, AJAX development with jQuery, and more. The future of the web is realtime. Grab your hoverboard. Introduces you to the revolutionary capabilities of the HTML5 WebSocket API Gets you started with WebSocket immediately using the super-simple Pusher API Walks you through the development of a real-life realtime web app Gets you working with responsive layouts, jQuery, and AJAX development.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems